Solution Of Logistics Issues on The Basis of Intellectual Analysis Methods of Suppliers - Axundjanova Moxira Azamovna (Zien Journals, 2021)
Analysis is one of the most important functions of management of any economic phenomena, including logistic processes. Logistics efficiency is measured not only by its specific indicators, but also impact on the economic and financial results of enterprises using logistic approaches. Research methods of logistics activities allow you to evaluate the effectiveness of the system of movement of material flow and provide an opportunity to identify areas for improvement.
Keywords: Specific indicators; material flow; scientific and practical publications